A phenomenological study exploring parental involvement among role model students in a private secondary school - Rode, Nigel Evan; Wong, Su Luan (Universiti Putra Malaysia Press, 2016)
This qualitative phenomenological study was conducted with the purpose of understanding the role parents played and exploring the extent of parental involvement in bringing up their children to become role model students in a private secondary school setting. This study was conducted based upon the viewpoints of ten role model students from a private secondary school based in Cheras, Kuala Lumpur. Five common interrelated themes were obtained and exhaustively described in the findings of this study. The study found in order to raise a generation of student role models, parental involvement was seen through the laying of strong foundations which came in the form of the upbringing of their children from young, and by giving them the freedom and space to learn, grow and mature as the child grew older, together with providing the best the parents could offer towards their child’s education, and in trusting private education that would continue to build upon the foundations first laid by the parents.